2021
DOI: 10.1111/ina.12810
|View full text |Cite
|
Sign up to set email alerts
|

Associations of indoor carbon dioxide concentrations, air temperature, and humidity with perceived air quality and sick building syndrome symptoms in Chinese homes

Abstract: The indoor environment influences occupants' health. From March 1, 2018, to February 28, 2019, we continuously monitored indoor temperature (T), relative humidity (RH), and CO 2 concentration in bedrooms via an online system in 165 residences that covered all five climate zones of China. Meanwhile, we asked one specific occupant in each home to complete questionnaires about perceived air quality and sick building syndrome (SBS) symptoms at the end of each month. Higher CO 2 concentration was significantly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 64 publications
3
22
0
Order By: Relevance
“…Ventilation work has helped to normalize the symptoms of SBS. Carbon dioxide and poor ventilation seem to be the main causes of SBS 6,36 . In line with the literature, we demonstrated the impact of insufficient ventilation on symptoms 37 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Ventilation work has helped to normalize the symptoms of SBS. Carbon dioxide and poor ventilation seem to be the main causes of SBS 6,36 . In line with the literature, we demonstrated the impact of insufficient ventilation on symptoms 37 .…”
Section: Discussionsupporting
confidence: 90%
“…Carbon dioxide and poor ventilation seem to be the main causes of SBS. 6,36 In line with the literature, we demonstrated the impact of insufficient ventilation on symptoms. 37 38,39 The dose-response relationship is typically evaluated to investigate the causes of the onset of SBS symptoms.…”
Section: Sick Building Syndrome Work Environment and Ventilation Worksupporting
confidence: 88%
“…[156][157][158][159] In an extensive 1-year study in 165 Chinese residences, it was shown that, in addition to temperature and humidity, the carbon dioxide content also influences the perceived air quality. 160 This again underlines that carbon dioxide is also a key parameter in assessing air quality. Several studies have shown that the cognitive abilities of people decrease with increasing carbon dioxide content in the breathing air.…”
Section: Human Perception Of Temperaturementioning
confidence: 95%
“…The analysis flowchart is presented in Figure 1. The correlations among the health risk and the indoor parameters were approved, and the monitoring of the relative humidity (RH), CO 2 , and T was suggested for improving the IAQ [37]. The main factors that affect IAQ in the vehicles included the humidity percentage, CO 2 , T, the airflow rate and direction, the type of the utilized air filter [38][39][40], the seat arrangement, and the displacement of ventilation [19,41].…”
Section: Methodsmentioning
confidence: 99%